Excision arthroplasty of the hip joint in dogs and cats - Off, W.; Matis, U. (Veterinary and Comparative Orthopaedics and Traumatology, 2010)
From 1978 to 1989, 132 dogs and 51 cats underwent femoral head and neck ostectomy at the Department of Veterinary Surgery, Ludwig-Maximilians University, Munich, Germany. Clinical and radiographic re-evaluations were carried out an average of four years postoperatively in 81 (44%) of the animals, and gait analysis was also done in 17. The functional results were rated good in 38% of patients, satisfactory in 20%, and poor in 42%. However 96% of the owners were satisfied with the results. Kinetic and kinematic measurements showed that although femoral head and neck resection alleviated pain, it resulted in functional deficits in small as well as large breed dogs. These deficits were not visible during rapid movement.This article was originally published in 1997 in the journal Tierärztliche Praxis. Both authors have approved the re-publication of this article in English, for which they have provided the translation of as well. Original citation: Off W, Matis U. Resektionsarthroplastik des Hüftgelenkes bei Hunden und Katzen. Klinische, röntgenologische und ganganalytische Erhebungen an der Chirurgischen Tierklinik der Ludwig-Maximilians-Universität München. Tierärztl Prax 1997 25: 379–387.
Keywords: Dog; cat; hip joint; femoral head and neck ostectomy; clinical and radiographic findings; gait analysis